Demographic forecasts and volatility of investment rates vs. labor productivity trajectories - Bolińska, Monika; Dykas, Paweł; Mentel, Grzegorz; Misiak, Tomasz (Journal of Business Economics and Management, 2019)
In the article the authors attempted to develop the neoclassical model of economic growth, repealing two assumptions regarding the Solow growth model. First of all, the authors assume that the growth path of the number of employees is increasing asymptotically to a fixed value, not to infinity as in the Solow model. The growth paths of the number of employees were determined based on demographic forecasts and the economic activity coefficient, which in the paper is understood as the ratio of the number of employees to the number of people. Secondly, the authors repeal the assumption of a fixed investment rate by taking into account the trend of changes in investment rates (a growing or declining trend). The theoretical model obtained was subjected to calibration and then numerical simulations were carried out. It was assumed that investment rates in the Polish economy decrease (from 25 to 15%) or grow (from 15 to 25%). Numerical simulations were based on demographic forecasts for the Polish economy up to 2050. Moreover, two scenarios for shaping the economic activity coefficient were considered: realistic one when in the period 2000-2050 it increased from 0.38 to 0.5. In the second scenario, it was optimistic that the increase would be 50% higher than in the first option and in 2050 it would reach 0.56. Important conclusions from the study can be presented as follows: (i) the population decline can be offset by the growing economic activity rate and therefore does not have a negative impact on economic growth, (ii) the negative impact of demographic changes on economic growth can also be offset by growing investment rates.